Renormalization of Group Field Theories for Quantum Gravity: New Computations and Some Suggestions - Finocchiaro, Marco; Oriti, Daniele (Frontiers in Physics, 2021)
We discuss motivation and goals of renormalization analyses of group field theory models of simplicial 4d quantum gravity, and review briefly the status of this research area. We present some new computations of perturbative Group field theories amplitudes, concerning in particular their scaling behavior, and the numerical techniques employed to obtain them. Finally, we suggest a number of research directions for further progress.